Kejadian Stunting Berdasarkan Jenis Kelamin Dan Usia Di Wilayah Kerja Puskemas Kalisat - Imania Zulfa; Ristya Widi Endah Yani; I Dewa Ayu Ratna Dewanti (Fakultas Kedokteran Gigi Universitas Jember, 2023)
Stunting is a chronic condition characterized by the poor condition of the child or the inhibition of the child's linear growth due to the accumulation of various factors that occur over a long time. This situation can be seen based on the z-score of height according to age less than -2 standard deviation (SD) which is classified as short and very short. To find out the incidence of stunting by gender and age in the working area of the Kalisat Health Center in 2020. Descriptive research using secondary data from patient KIA data in February 2020. From the research that has been done, it can be concluded that the incidence of stunting in toddlers is mostly male and toddlers aged 24-36 months.